Genetically engineered fusion of MAP‐1 and factor H domains 1–5 generates a potent dual upstream inhibitor of both the lectin and alternative complement pathways. Issue 12 (10th August 2015) - Nordmaj, Mie Anemone; Munthe‐Fog, Lea; Hein, Estrid; Skjoedt, Mikkel‐Ole; Garred, Peter
ABSTRACT: Inhibition of the complement cascade has emerged as an option for treatment of a range of diseases. Mannose‐binding lectin/ficolin/collectin‐associated protein (MAP‐1) is a pattern recognition molecule (PRM)‐associated inhibitor of the lectin pathway. The central regulator of the alternative pathway (AP) is complement factor H (FH). Our aim was to design a dual upstream inhibitor of both human lectin and APs by fusing MAP‐1 with a part of FH. There were 2 different recombinant chimeric proteins comprising full‐length human MAP‐1 and the first 5 N‐terminal domains of human FH designed. The FH domains were orientated either in the N‐ or C‐terminal part of MAP‐1. The complement inhibition potential in human serum was assessed. Both chimeric constructs displayed the characteristics of the native molecules and bound to the PRMs with an EC50 of ∼2 nM. However, when added to serum diluted 1:4 in a solid‐phase functional assay, only the first 5 N‐terminal domains of complement FH fused to the C‐terminal part of full‐length MAP‐1 chimeric construct were able to combine inhibition of lectin and AP activation with an half maximal inhibitory concentration of ∼ 100 and 20 nM, respectively. No effect was seen on the classical pathway. Fusion of MAP‐1 with FH domains represents a novel therapeutic approach for selective targeting upstream and central complement activation at sites of inflammation.—Nordmaj, M. A., Munthe‐Fog, L., Hein, E., Skjoedt, M.‐O., Garred, P. Genetically engineered fusion of MAP‐1 and factor H domains 1–5 generates a potent dual upstream inhibitor of both the lectin and alternative complement pathways. FASEB J. 29, 4945–4955 (2015). www.fasebj.org